Cognitive dysfunction associated with COVID-19: A comprehensive neuropsychological study. (June 2022) - Delgado-Alonso, Cristina; Valles-Salgado, Maria; Delgado-Álvarez, Alfonso; Yus, Miguel; Gómez-Ruiz, Natividad; Jorquera, Manuela; Polidura, Carmen; Gil, María José; Marcos, Alberto; Matías-Guiu, Jorge; Matías-Guiu, Jordi A.
Abstract: Objective: Recent evidence suggests that patients suffering post-acute COVID syndrome frequently report cognitive complaints, but their characteristics and pathophysiology are unknown. This study aims to determine the characteristics of cognitive dysfunction in patients reporting cognitive complaints after COVID-19 and to evaluate the correlation between cognitive function and anxiety, depression, sleep, and olfactory function. Methods: Cross-sectional study involving 50 patients with COVID-19 reporting cognitive complaints 9.12 ± 3.46 months after the acute infection. Patients were evaluated with a comprehensive neuropsychological protocol, and scales of fatigue, depression, anxiety, sleep and an olfactory test. Normative data and an age- and education matched healthy control group were used for comparison. Results: COVID-19 patients showed a diminished performance on several tests evaluating attention and executive function, with alterations in processing speed, divided attention, selective attention, visual vigilance, intrinsic alertness, working memory, and inhibition; episodic memory; and visuospatial processing. Cognitive performance was correlated with olfactory dysfunction, and sleep quality and anxiety to a lesser extent, but not depression. Conclusions: Patients with COVID-19 reporting cognitive symptoms showed a reduced cognitive performance, especially in the attention-concentration and executive functioning, episodic memory, and visuospatial processing domains. Future studies are necessary to disentangle the specific mechanisms associated with COVID-19 cognitive dysfunction.